The Optimization of The Giving Cow Manure and Wood Charcoal to the Growth of Salam (Syzygium polyanthum (Wight) Walp.) on Contaminated Soil by Used Engine Oil - Basuki Wasis; Ronaldo H Naiborhu (Jurnal Silvikultur Tropika, 2021)
Illegal disposal of used oil causes soil contamination which can damage and reduce the soil productivity. Planting salam (Syzygium polyanthum) with the addition of cow manure and wood charcoal is expected to improve the characteristics of soil that was contaminated by used oil. This study analyzed the effect of giving cow fertilizer and wood charcoal on the growth of salam and determining the optimal dose to increase the growth of salam on contaminated soil by used oil. This study used a factorial completely randomized design (CRD) with two factors; that is cow manure and wood charcoal and using 60ml/kg of soil contaminated with used oil. This study shows that giving 90 gram of cow manure and 40 gram of wood charcoal gave the best response to total wet weight and root length. The application of 90 gram of cow manure and 20 gram of wood charcoal gave the best response to the diameter and application of 90 gram of cow manure gave the best response to the total dry weight of salam seeds. Giving cow manure and wood charcoal can also reduce the Pb content by 0,43 ppm. Keywords: cow manure, Syzygium polyanthum, used oil, wood charcoal